The World after COVID-19: the Necessity of Transition to a New Development Paradigm - V. M. Bondarenko (Модернизация, инновация, развитие, 2021)
This article is a continuation of a large-scale research devoted to the identification of patterns of human community development, which has been conducted by the author for many decades.Purpose: is to study the possible transformation of the world after the COVID-19 pandemic from the perspective of the need to switch to a new, crisis-free development paradigm, which is a logical continuation of the previous author's works.Methods: the study is based on the application of a complex of general scientific methods, including analysis, generalization, comparison, etc., and is based on an interdisciplinary approach. The results and conclusions of the work are based on the use of the author's methodological tools, which were formed within the framework of the general research direction.Results: the article analyzes the current state of the global world in the absence of effective ways out of the deepest crisis that has long gripped almost the entire world and has been multiplied by the COVID-19 pandemic. The study of the fundamental works of foreign scientists has shown that their main thesis is that the future of the world lies in the transition to a new development paradigm (NDP), but to fully understand it, it is necessary to develop a new scientific paradigm (NSP). Based on the use of the author's development of the NSP, it is demonstrated that the future of the world depends on the choice of a development model. The author has proved the necessity and possibility of transition to a new development paradigm based on the synchronous development and implementation of a single development strategy for the global world and each country separately.Conclusions and Relevance: after the COVID-19 pandemic, the world will change only if there is a transition to a new crisis-free paradigm for the development of the human system. The NSP developed by the author can become the tool that allows you to give a complete understanding of the NDP, and see what the world can and should be like after the coronavirus pandemic.